The Effect of Teacher Training, Technology Literacy and Self-Efficacy for Integrating Technology - Agnes Silvia Waren; Lantip Diat Prasojo (FKIP Universitas Lampung, 2024)
The Effect of Teacher Training, Technology Literacy and Self-Efficacy for Integrating Technology. Objectives: The objects in this research are teacher training, teacher technological literacy, teacher self-efficacy and integration of technology in learning. Methods: This research uses quantitative methodology through path regression analysis where data processing includes testing classical assumptions, testing path equation model regressions, and then determining the magnitude and direction of correlation between path variables. The research data source was obtained from Transformational High School in Gunung Kidul Regency. There were 182 teachers who were willing to be respondents to fill out a research questionnaire. It comprises of 151 questions, which are valid and reliable from a Likert scale model. The sample size is quantified based on the Slovin formula in which the minimum required sample is 143 samples. Findings: The findings reveal that the integration of learning technology in direct relationships is contributed from teacher training and literacy technology at 8.6%, from self-efficacy at 6.8% and from teacher training, technology literacy, and teacher self-efficacy at 47% when analysed simultaneously. For the indirect path, the contribution of training to technology integration is 0.64% which is mediated by literacy, and 7.29% which is mediated by self-efficacy, while for the indirect literacy path which is mediated by self-efficacy in integrating technology is 0.16%. Conclusion: In conclusion, there is a significant, consistent relationship, both directly and indirectly, for each variable in the correlation path among teacher training, technological literacy and teacher efficacy in facilitating the integration of technology into learning. Keywords: training, literacy, self-eficacy, technology, integration.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202467